Aquilaria yunnanensis S.C. Huang (Thymelaeaceae), A New Record for the Flora of Vietnam - Van Sam, Hoang; Cerboncini, Claudio; Trung Hieu, Duong; Thi Hang, Hoang; Van Huan, Ha; Ngoc Hai, Tran; Bao Thanh, Le; Thanh Tam, Do; Thi Tho, Nguyen; Thanh Tuan, Nguyen; Van Chu, Tran; The Nha, Nguyen; et al. (Forest and Society, 2019)
Aquilaria yunnanensis S.C. Huang (Thymelaeaceae), known to be endemic to Yunnan, is recorded for the first time from Dong Son Ky Thuong Nature Reserve, Quang Ninh Province, Vietnam. A taxonomic description and DNA analysis based on our Vietnamese collections are presented, together with information on its distribution, habitat and colour photographs.